A review of the milling process to fabricate a dimple structure / Sharudin Hassan...[et al.] - Hassan, Sharudin; A. Ghani, Jaharah; Che Haron, Che Hassan; Mohd Dali, Mohd Nor Azam; Rizal, Muhammad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Surface texture has become the main element in reducing friction on any moving surface. Dimple structure, is a surface texture that is produced through various processes like electrochemistry, electric-term, electrolysis, laser and machining. Vibration-assisted machining technique is the latest technique in the dimple structure fabrication. It has been proven to impact the roughness of the surface machined. Its application in the dimple structure fabrication is still at an experimental level as compared to the vehicle component surface. In this review, the dimple structure fabrication process via (turning milling) and vibration assisted technique are discussed to help the researchers understand the suitable dimple structure fabrication process to be applied on the vehicle lubrication system